Knowledge And Attitude Factors Of Nurses Dealing With Atraumatic Application Care To Child Patient - Suminar, Cucum -; Yulianti, Mona; Kurnaesih, Lilis (Universitas Muhammadiyah Kalimantan Timur, 2022)
Atraumatic care can reduce the anxiety of children or parents during the hospitalization. The implementation of atraumatic care are affected by many factors, such as internal and external factors. The purpose of this study was to determine the nurse's knowledge and attitude related to the application of atraumatic care in pediatric patients in room Tanjung RSUD Sumedang in 2019. The study was a descriptive analytical approach. The sample in this study were all nurses in Tanjung Room consist of 33 people taken using total sampling techniques. Descriptive analysis was used to describe the characteristics of respondent, nurses' knowledge and attitudes about atraumatic care, and the application of atraumatic care by nurses. Therefore bivariate analysis was done using Rank Spearman test to see the relationship between nurses' knowledge and attitudes with the application of atraumatic care. The results of this study showed that the majority of respondents have less knowledge about atraumatic care (90.9%), most nurses showed a positive attitude towards the application of atraumatic care (90.9%), most of nurses have applied atraumatic care well (72.7%). From the bivariate analysis, known that there is no relationship between the knowledge and attitudes of nurses regarding the implementation of atraumatic care with the application of atraumatic with the p value for knowledge (0.751) and the p value for attitude (0.812). For further researchers to explored the factors that influence the application of atraumatic care by using different approaches and methods so that research will be more varied.